(3cJGH GdYjfs - (3GdNdjd Hf CMeO Hf YeQh Hf Jeje GdaQGgjOj GdCROj GdjMeOj, CHh YHO GdQMef,J (B170 (3g` s
(3ChdgG (B:s
(3HGddg fgJOi hYdjg fJhcd eG JcdeJ eOGQ cdGe GdYQH hCdaGXge hdGjNQL efgG efg TF s
(3BNQgG (B:s
(3BNQ GdeLdO GdKGfi adh JcdaJ ef GdCjI GTJbGbkG Ydi bjGS YdGeI eYdeI dbdJ BjI aCjGg bO CjjJ aGYde Gf TGA Gddg JeJ MQha GdeYJdI HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B112s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1441s
Keywords: (3GddZIs